(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Law enforcement receives a First Information Report to begin the investigation and create a legalrecord. In order to protect the rule of law, protect rights, and promote transparency in early criminalinvestigations, the Code of Criminal system standardized the FIR system. FIRs let victims reportcrimes and seek justice, but false or malicious ones can ruin the accused. FIRs' procedural issuesmight impede justice as they balance victim protection and presumption of innocence. The advent ofdigital FIR procedures has increased access, transparency, and reduced record tampering. Legalprocesses, evidence recording, victim empowerment, legal protection, police action framework, courtsupervision, statistics and policy analysis, transparency and accountability, and aiding legal actiondepend on the FIR system. Complex First Information Report (FIR) registration might harm criminaljustice. Due to faulty reporting, delayed registration, police discretion and prejudice, fear of reprisal,FIR abuse, disinformation, poor police training, bureaucratic challenges, technological obstacles,and local intervention. Law enforcement and citizen rights are balanced in FIR registration andadministration under the CrPC and IPC. Police structure, operation, and FIR filing are governed bythe 1861 Police Act. In State of Haryana v. BhajanLal and Khatri v. Bihar, courts interpretedlegislation to clarify FIRs and criminal prosecutions. These past events demonstrate the importanceof accountability and monitoring to prevent future offences and protect basic rights in prison.Coercion and fraud threaten the First Information Report, which the criminal justice system relies on